Educational situation of Portuguese ciganos: social changes versus social continuities - Mendes, Maria Manuela (2021)
The purpose of this chapter is to present and discuss the main impacts of Portuguese public policies in the area of education in Portugal, since 25 April 1974. To this end, diversified information was collected, processed and analysed involving legal and other documents about these national policies, especially those of greater impact on Ciganos, in addition to thorough mapping of ongoing projects of local and social support in the Lisbon and Porto metropolitan areas, where the empirical research is being carried out. At a later stage, interviews were held with technical staff, project coordinators and local institutions, as well as Ciganos and their families. The purpose of using various data collection techniques is to capture the reality experienced by Cigano individuals and families, namely patterns of continuity and social change, particularly in the area of education, through triangulation between the discourses of informants and scientific knowledge already consolidated in these matters. We present a critical and reflexive interpretation of the policy orientations and achieved social rights, focusing on narratives of Ciganos, stakeholders and school representatives centred on what has changed in the school trajectories of Ciganos, in terms of continuity, success and permanence in public education.